James Clavell's Shōgun [videorecording (DVD)] - London, Jerry; Chamberlain, Richard, 1935-; Mifune, Toshiro, 1920-1997; Shimada, Yōko, 1953-; Clavell, James (Paramount Home Video, 2003)
John Blackthorne is a ship-wrecked English navigator who becomes both an observer and a participant in historic changes in Japan during the Tokugawa, or, Edo period. Toranaga is a feuding warlord vying to become the supreme military dictator, or shōgun. Blackthorne is drawn into the turmoil and becomes determined to be the first foreigner to become a samurai warrior.